BODY COMPOSITION BY DXA IN ELDERLY MEN (Fiep Bulletin - online, 2014)
The increase in life expectancy is increasing the amount of elderly population comes in recent decades and consequently related studies, especially those related to health. One aspect is the change in body composition aiming the goal of the study that aimed to assess body composition in elderly men by means of the technique of X-ray absorptiometry (DXA). The methodology is epidemiologically with 85 men with 69,55±5,89 years residents in Big Vitoria. Measured the percentage of fat (%F) determined by DXA. The results were: body mass77,32±13,35kg; height 1,66±0,06m;  %F de 30,06±7,16; lean body mass of53,69±6,98kg; weightfat 23,73±9,03kg; muscle weight of 31,79±4,82kg; bone weight of 3,34±0,58kg and residual weight 18,55±3,2kg. It was concluded that the percentage of fat is high according to Pollock and Wilmore (1993) and it is important to broaden the debate and the development of research on the anthropometric assessment of elderly patients with clinical applicability in the context of epidemiological and basic network health.
Keywords: Body Composition; DXA; elderly